2017
DOI: 10.1002/ijc.31103
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol consumption, variability in alcohol dehydrogenase genes and risk of renal cell carcinoma

Abstract: Alcohol consumption has been associated inversely with renal cell carcinoma (RCC) risk; however, no study has examined effect modification by germline variation in alcohol-metabolizing genes. We investigated whether the association between alcohol intake and RCC risk is modulated by germline variants in alcohol dehydrogenase genes in a large case-control study. Data from 652 RCC cases and 1,366 non-cancer controls were analyzed. Alcohol intake was assessed using a standardized risk factor questionnaire. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
(150 reference statements)
1
10
1
2
Order By: Relevance
“…In the current study, even light to moderate levels of lifetime alcohol consumption appeared to increase most of the upper aerodigestive and gastrointestinal cancers . In contrast to the patterns observed in Western settings, we observed no protective effects of light to moderate lifetime alcohol consumption for colorectal and kidney cancers. For breast and prostate cancer, different pathways such as elevations of circulating sex hormone levels (ie, estrogens and androgens) by alcohol use may explain the alcohol‐related cancer risk at even light to moderate levels of lifetime alcohol consumption .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, even light to moderate levels of lifetime alcohol consumption appeared to increase most of the upper aerodigestive and gastrointestinal cancers . In contrast to the patterns observed in Western settings, we observed no protective effects of light to moderate lifetime alcohol consumption for colorectal and kidney cancers. For breast and prostate cancer, different pathways such as elevations of circulating sex hormone levels (ie, estrogens and androgens) by alcohol use may explain the alcohol‐related cancer risk at even light to moderate levels of lifetime alcohol consumption .…”
Section: Discussioncontrasting
confidence: 99%
“…Drinking alcohol is a contributor to the overall cancer burden. In Western settings, alcohol‐related cancer risk has been characterized as a J‐shape pattern in some instances (colorectal and kidney cancers), and this suggests potential protective effects of alcohol . However, in 2018, the American Society of Clinical Oncology stated that more than 5% of new cancer cases were attributable to alcohol consumption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, alcohol tolerance varies greatly from person to person, and some nations consume more alcohol than others. Although studies on individual differences in alcohol consumption and CKD are limited, existing studies have found that individual variation in an alcohol dehydrogenase gene may play a role [98], but more studies are needed to confirm these findings.…”
Section: Association Between Alcohol Consumption and Chronic Kidney Dmentioning
confidence: 99%
“…Multiple studies have assessed gene-environment interactions in RCC and ccRCC. RCC risk has been found to be associated with interactions between alcohol consumption and ADH7 26 ; sodium and hypertension and AGTR, AGT and ACE 31 ; calcium and vitamin D intake and RXRA 28 ; tobacco smoking and NAT2, CYP1A1 and GSTM1 25 ; and meat-cooking mutagens and ITPR2 and EPAS1 27 . To our knowledge, we are the first to study gene-environment interactions between the selected VHL and HIF1A SNPs and smoking, hypertension, BMI and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%